Diagnostic accuracy of interlimb differences of ultrasonographic subcutaneous tissue thickness measurements in breast cancer-related arm lymphedema - (:unkn) unknown (My University, 2019)
Use of ultrasound as an assessment technique for lymphedema has been increasing with measurement of subcutaneous tissue thickness used for both assessment and treatment outcome. Reliability of ultrasound examination of the thickness of the skin and subcutaneous tissue have been studied. However, interlimb differences of ultrasonographic subcutaneous tissue thickness have not been explored. This study aimed to establish diagnostic accuracy of interlimb differences of ultrasonographic subcutaneous tissue thickness measurements in breast cancer-related arm lymphedema. We compared the truncated cone method by using circumference measurements and interlimb differences of ultrasonographic subcutaneous tissue thickness measurements to evaluate the diagnostic accuracy of interlimb differences of ultrasonographic subcutaneous tissue thickness measurements. Sensitivity, specificity, receiver-operating characteristic (ROC) curve, and area under the curve (AUC) were used. Analysis of ROC curves yielded area under the curve (AUC) of 0.804 (p=0.002). ROC analysis identified 0.17cm as the cut-point for differentiating between tissue with and without lymphedema resulting in a sensitivity of 79.3% and specificity of 69.2%.
Keywords: Adult; Female; Humans; Middle Aged; Reproducibility of Results; diagnosis; Ultrasonography; ultrasound; ROC Curve; Arm; Organ Size; breast cancer; Subcutaneous Tissue; assessment; Breast Cancer Lymphedema; lymphedema; measurement